Swarm Intelligence: An Overview - Panchal, VK; Jain, Ankit; Singh, Rashmi (Gyan Management Journal, 2007)
Nature and biology have been a rich source of inspiration for computer scientists. Genetic algorithms, neural networks and siniulated annealini are examples where different natural processes have been mimicked algorithmically w successfully solve importanl practical problems. More recent[)